Exploration of β-glucosidase-producing microorganisms community structure and key communities driving cellulose degradation during composting of pure corn straw by multi-interaction analysis. (1st January 2023) - Han, Yue; Liu, Wanying; Chang, Nuo; Sun, Lei; Bello, Ayodeji; Deng, Liting; Zhao, Liyan; Egbeagu, Ugochi Uzoamaka; Wang, Bo; Zhao, Yan; Zhao, Mingming; Bi, Ruixin; et al.
Abstract: Poor management of crop residues leads to environmental pollution and composting is a sustainable practice for addressing the challenge. However, knowledge about composting with pure crop straw is still limited, which is a novel and feasible composting strategy. In this study, pure corn straw was in-situ composted for better management. Community structure of β-glucosidase-producing microorganisms during composting was deciphered using high-throughput sequencing. Results showed that the compost was mature with organic matter content of 37.83% and pH value of 7.36 and pure corn straw could be composted successfully. Cooling phase was major period for cellulose degradation with the highest β-glucosidase activity (476.25 μmol·p-Nitr/kg·dw·min) and microbial diversity (Shannon index, 3.63; Chao1 index, 500.81). Significant compositional succession was observed in the functional communities during composting with Streptomyces (14.32%), Trichoderma (13.85%) and Agromyces (11.68%) as dominant genera. β-Glucosidase-producing bacteria and fungi worked synergistically as a network to degrade cellulose with Streptomyces (0.3045**) as the key community revealed by multi-interaction analysis. Organic matter (−0.415***) and temperature (−0.327***) were key environmental parameters regulating cellulose degradation via influencing β-glucosidase-producing communities, and β-glucosidase played a key role in mediating this process. The above results indicated that responses of β-glucosidase-producing microorganisms to cellulose degradation were reflected at both network and individual levels and multi-interaction analysis could better explain the relationship between variables concerning composting cellulose degradation. The work is of significance for understanding cellulose degradation microbial communities and process during composting of pure corn straw. Graphical abstract: Image 1 Highlights: 1. Composting could be conducted successfully with pure corn straw. 2. Cooling phase was the main phase for cellulose degradation in composting. 3. Cellulose degradation was driven by functional bacteria and fungi synergistically. 4. Organic matter, temperature, Streptomyces were key factors of cellulose degradation. 5. Cellulose degradation could be better explained by the multi-interaction analysis.